Specific attention disorders in drivers with traumatic brain injury. (May 2013) - Masson, Marjolaine; Michael, George Andrew; Désert, Jean-François; Rhein, François; Foubert, Lucie; Colliot, Pascale
<x xml:space="preserve">Abstract</x> Objective: To highlight the impact of the increasing attentional load on performance of both normal drivers and drivers with traumatic brain injury. Background: Patients with brain injury have a higher accident risk than people with no brain injury [1], probably as a result of persistent attention disorders. Method: Ten patients and 10 paired controls took part in a computerized selective attention task involving specific attentional processes. They were asked to monitor a speedometer and to ignore sudden changes in the surrounding environment in three separate experimental situations involving different attentional load. Results: Although, in the control situation, patients' results were equivalent to controls', they displayed specific disorders in more complex situations where the attentional load increased. Conclusion: These difficulties may have a negative impact on real driving situations.